EAFD-AA7075 composites fabricated by Spark Plasma Sintering (SPS) : experiments and electro-thermo-mechanical-microstructural simulation - SILVA, Elder Soares da (2022)
The use of industrial waste, such as Electric Arc Furnace Dust (EAFD), the generic name for powdered waste recovered after the production of steel in electric-arc furnaces, as reinforcement in AMCs is still little explored, although it has shown potential to improve some mechanical properties of the base material, such as hardness and strength. Aiming to propose a new alternative for the reuse of EAFD, AA7075 matrix composites reinforced with EAFD, using different fractions and particle sizes, were produced. The starting powders were processed using a SPEX type ball mill. The densification of the EAFD-AA7075 samples was performed using the innovative Spark Plasma Sintering (SPS) technique, in a single step, where the sample was heated from room temperature at a rate of 100 °C/min to a temperature of 550° C, this temperature was maintained for 15 min or 30 min, depending on the sample. During this process, a uniaxial pressure of 100 MPa was applied. No further heat treatment is carried out. To evaluate the influence of EAFD fraction and particle size on the mechanical properties and the microstructure of the composite material, Vickers microhardness, optical microscopy and scanning electron microscopy (SEM) tests were carried out on the sintered samples. Observations in SEM show that the distribution of the reinforcement particles in the material is homogeneous, without agglomeration of the particles. The microhardness of AA7075/EAFD composites tends to increase with increasing EAFD content, showing that EAFD presents promising potential to be applied as reinforcement in AA7075 matrix composites. The maximum increase in microhardness occurred using EAFD with particle size smaller than 53 μm (termed G1), increasing from 108 to 168 HV with the EAFD contents from 0 to 15% by weight, respectively, corresponding to a maximum increase of 55.6% over the microhardness of the base material. Finite Element Method (FEM) was used as a predictive tool to obtain the best densification route by the SPS technique. By comparing the results obtained through simulation with the experimental results, it was possible to notice that the densification curves are very similar, which validates the study and proves that FEM is a good predictive tool for the SPS process and the resulting material properties.